THE EXISTANCE OF PERGURUAN KEBATINAN SANDHI MURTI INDONESIA IN THE FIELD OF KANURAGAN IN BALI - Gayatri, Ida Ayu Made; Ardika, I Wayan Ardika; Arsana, I Gusti Ketut Gde (E-Journal of Cultural Studies, 2015)
Perguruan Kebatinan Sandhi Murti Indonesia is establised by I Gusti Ngurah Harta on 27 th April 1990 in Denpasar City, Bali. Practice of kanuragan is identical to the stigma of violence, the practice of inner power and pangleakan associated with black magic, so this study aims to analyze and answer the formulation of the problems on the existence of social practices of Sandhi Murti in the field of kanuragan in Bali. This study is constructed as a cultural studies. The results of study showed the existence of Sandhi Murti in the field of kanuragan in Bali for 24 years (1990-2004) is characterized by the development of forms of activity in sports as well as in the arts, mysticism, economy and politics. Sandhi Murti social practices are also undergoing expansion area of activity in the branch organization in Tabanan Bali and Sandhi Murti Bulgaria in Europe, as well as developed personally by members overseas such as Australia, America, Russia and others. Sandhi Murti practices in the field of kanuragan is based on the teachings of siwa tantra (tantric), or siwa bhairawa, kandapat and dasaksara . Functions of kanuragan practiced by Sandhi Murti, such as : psychosomatic and psycho-kinetics therapy; commodity and recreational; magical function, social and cultural functions.The significance of social practices of Sandhi Murti develop social capital through group of solidarity. Significance of cultural transformation Sandhi Murti kanuragan practices reflected the cultural inheritance of tantric into organizational habitus .
Keywords: social practice, organization, Sandhi Murti, kanuragan, transformation mystical culture of Bali.